Pengaruh Perputaran Modal Kerja dan Fixed Asset Turnover terhadap Net Profit Margin pada Perusahaan Sektor Semen - Arif Tribowo; Yenni Samri Juliati Nst; Nurwani, Nurwani (AKUA: Jurnal Akuntansi dan Keuangan, 2024)
This research aims to determine the effect of working capital turnover and fixed asset turnover on the net profit margin sector in sub-cement companies listed on the Indonesia Stock Exchange for the 2016-2021 period. This research uses a quantitative method which has a population of 5 sector cement companies listed on the Indonesia Stock Exchange in 2016-2021. The sampling technique in this research is the saturated sample method. Saturated sampling is a sampling technique when all members of the population are used as samples. The results of the first research show that working capital turnover has an effect on Net Profit Margin and has a positive direction in cement sub-sector companies listed on the Indonesia Stock Exchange for the 2016-2021 period. The results of the second study show that fixed asset turnover has no effect on net profit margin. And the results of the third research show that the fcount value is 4.778 > the ftable value 3.35 and the sig value. 0.017 < 0.05. Thus, the conclusion is that there is a significant influence between working capital turnover and fixed asset turnover which together influence the net profit margin in cement sub-sector companies listed on the Indonesia Stock Exchange for the 2016-2021 period.